PEGylated Domain I of Beta-2-Glycoprotein I Inhibits Thrombosis in a Chronic Mouse Model of the Antiphospholipid Syndrome - Willis, Rohan; McDonnell, Thomas C. R.; Pericleous, Charis; Gonzalez, Emilio B.; Schleh, Alvaro; Romay-Penabad, Zurina; Giles, Ian P.; Rahman, Anisur (Frontiers in Immunology, 2022)
Antiphospholipid syndrome (APS) is an autoimmune disorder in which autoantibodies cause clinical effects of vascular thrombosis and pregnancy morbidity. The only evidence-based treatments are anticoagulant medications such as warfarin and heparin. These medications have a number of disadvantages, notably risk of haemorrhage. Therefore, there is a pressing need to develop new, more focused treatments that target the actual pathogenic disease process in APS. The pathogenic antibodies exert their effects by interacting with phospholipid-binding proteins, of which the most important is beta-2-glycoprotein I. This protein has five domains, of which the N-terminal Domain I (DI) is the main site for binding of pathogenic autoantibodies. We previously demonstrated bacterial expression of human DI and showed that this product could inhibit the ability of IgG from patients with APS (APS-IgG) to promote thrombosis in a mouse model. Since DI is a small 7kDa protein, its serum half-life would be too short to be therapeutically useful. We therefore used site-specific chemical addition of polyethylene glycol (PEG) to produce a larger variant of DI (PEG-DI) and showed that PEG-DI was equally effective as the non-PEGylated DI in inhibiting thrombosis caused by passive transfer of APS-IgG in mice. In this paper, we have used a mouse model that reflects human APS much more closely than the passive transfer of APS-IgG. In this model, the mice are immunized with human beta-2-glycoprotein I and develop endogenous anti-beta-2-glycoprotein I antibodies. When submitted to a pinch stimulus at the femoral vein, these mice develop clots. Our results show that PEG-DI inhibits production of thromboses in this model and also reduces expression of tissue factor in the aortas of the mice. No toxicity was seen in mice that received PEG-DI. Therefore, these results provide further evidence supporting possible efficacy of PEG-DI as a potential treatment for APS.